Sign Description on Sausage Party Movie Directed by Greg Tiernan and Conrad Vernon - Andika Andika; Ansor Putra; Arman Arman (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2023)
This study analyzes the signs that exist within the scope of cultural representation in the Sausage Party movie using Charles Sanders Peirce's semiotic theoretical approach. The purpose of this study is to analyze how culture is represented in the form of signs in the Sausage Party movie using Charles Sanders Peirce's Semiotic theory approach. The data source is taken from the film Sosis Party. This research uses a descriptive qualitative method. Data collection is done by searching and downloading, watching movies, classifying, and coding data. based on the analysis the researcher managed to find fifteen signs which were divided into several types of signs including, icon, index, symbol, qualisign, legsign, sinsign, rheme, dicent, and argument. Every sign that appears on the characters in this film has a very precise placement and cannot be separated from the rules of the culture that is being represented.